Systematic Literatur Review : Peningkatan Kemampuan Literasi Matematis dengan Model Pembelajaran Structured Inquiry - Amarta Prayuti; Wardhani Rahayu; Meiliasari Meiliasari (Universitas Muhammadiyah Surabaya, 2024)
In meeting the needs of modern society, students are required to have several competencies, one of which is Mathematical Literacy. One way to improve students' mathematical literacy skills is to apply a Structured Inquiry-based learning approach. The purpose of this research is to investigate the components in Structured Inquiry learning that can improve students' mathematical literacy skills. The method used was Systematic Literature Review (SLR) of 30 filtered articles. The articles reviewed were sourced from Sinta 1 - Sinta 3 indexed articles, Scopus rank Q1 - Q3, and several sources from the Ministry of Education and Culture. The results show that the Structured Inquiry learning model can be used as one of the approaches in learning to improve students' mathematical literacy skills. Some materials that can be used to maximise student learning outcomes include geometry, arithmetic, and calculation materials. Teacher guidance in applying the structured inquiry learning model will greatly determine student learning outcomes, especially in improving their mathematical literacy skills. Structured inquiry learning is more optimally applied at the elementary and junior high school levels. It is necessary to develop mathematical literacy questions in order to improve students' mathematical literacy skills. It is hoped that future researchers can examine more deeply other learning models that can improve students' mathematical literacy skills.